Narrow gender earnings gap in the urban areas of the People's Republic of China: To what extent does service economy matter? - Guochang Zhao (Asian Development Bank Institute (ADBI), 2020)
It is believed that jobs in the service sector generally require more brain-related rather than labor-related skills compared to those in the industrial sector, thus females should have a comparative advantage in the service sector. Using the data from the 2017 China Household Finance Survey, we investigate the relationship between the service economy and the gender earnings gap in the urban People's Republic of China (PRC). The descriptive analyses show that the service economy hires more workers and pays more than the industrial sector on average; meanwhile the female employment share and gender earnings gap in the service sector are also higher and narrower, respectively, than those in the industrial sector. However, the decomposition analyses illustrate that the composition effect is only about 10% of the total gender gap, and that the service economy contributes most or all of the total composition effect across the earnings distribution. The service economy widens and narrows the gender gap through the composition effect and structure effect, respectively, but the latter is not insignificant. Therefore, simply increasing the share of the service economy is not likely to narrow the gender earnings gap in urban PRC. The fact that females are less likely to enter the high-pay service subsectors is the main reason why the rise of the service economy cannot narrow the gender earnings gap in urban PRC.
Keywords: J16; O14; 330; gender earnings gap; service economy; OB decomposition; RIF regression; quantiles